Energy spectral efficiency tradeoff in downlink OFDMA network. (7th January 2014) - Li, Zhihang; Jiang, Huilin; Pan, Zhiwen; Liu, Nan; You, Xiaohu
Summary Spectral efficiency (SE) is an important metric in traditional wireless network design. However, as the development of high‐data rate services and rapidly increase of energy consumption, energy efficiency (EE) has received more and more attention. In this paper, we investigate the EE–SE tradeoff in downlink OFDMA network. Different from previous researches, we try to optimize EE and SE simultaneously. First, the problem is formulated as a multiobjective optimization problem (MOP), and its Pareto optimal set is characterized. Then, we convert the MOP to a single‐objective optimization problem (SOP) by the weighted linear sum method and show that it is neither quasi‐convex nor quasi‐concave. After that, a novel algorithm using particle swarm optimization is proposed to solve the SOP. Simulation results validate that the proposed algorithm can efficiently reduce total transmit power and improve EE, although the cost is sacrificing some SE, which could be used to design an flexible energy efficient network in the future.Copyright © 2014 John Wiley & Sons, Ltd.